2021
DOI: 10.1109/lgrs.2020.3003088
|View full text |Cite
|
Sign up to set email alerts
|

Depth Measurement Bias in Pulsed Airborne Laser Hydrography Induced by Chromatic Dispersion

Abstract: In contrast to topographic laser scanning, laser hydrography must take into account the presence of two media. A pulsed laser beam, which enters the water from the air at an oblique angle, is refracted at the air-water boundary in the direction of the plumb line. This change of direction described by Snellius' law is caused by a slower speed of the light wave in the water, the phase velocity. Light scattering caused by turbidity gives rise to further deviations from the straight path. Together, the slower spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Recent studies have found that the fixed refractive index of 1.33 is inappropriate [ 20 ]. Using a group velocity instead of the fixed refractive index can reduce the range-dependent bias of the water depth [ 38 ]. Therefore, the calculation of the in-water path has a significant effect on water bottom, especially in deep waters, which need to be carefully corrected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the fixed refractive index of 1.33 is inappropriate [ 20 ]. Using a group velocity instead of the fixed refractive index can reduce the range-dependent bias of the water depth [ 38 ]. Therefore, the calculation of the in-water path has a significant effect on water bottom, especially in deep waters, which need to be carefully corrected.…”
Section: Discussionmentioning
confidence: 99%
“…(Höhle 1971). Conventional refraction correction methods assume a constant value of n 2 = 1.33 for direction and range calculation (Schwarz et al 2020).…”
Section: Related Workmentioning
confidence: 99%
“…The numerical simulation is based on the separate observation of the beam path of each individual photon in the laser pulse and applies to the specific parameters selected as input variables. Furthermore, Schwarz et al (2020) present an approach in which the propagation time extension due to scattering effects is considered by using the group velocity instead of the phase velocity for range calculation. The slower group velocity represents the propagation speed of a laser pulse in a dispersive medium and was determined experimentally.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no studies systematically investigating the bias we introduce due to temperature measurements in a geothermal setting. Studies for the measurement bias are common in the field of remote sensing (i.e., Feng et al, 2016;Schwarz et al, 2020); however, their focus is entirely different. In remote sensing, the location of the measurements is subjected to uncertainties.…”
Section: Introductionmentioning
confidence: 99%